2021
DOI: 10.3389/fphar.2021.734654
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising the Perceptions of Pharmacists Practicing Clinical Pharmacy in South Africa—Do We Practice what We Preach?

Abstract: The National Department of Health published their Quality Standards for Healthcare Establishments in South Africa and introduced the National Health Insurance, with the pilot phase that commenced in 2012. The system requires an adequate supply of pharmaceutical personnel and the direct involvement of clinical pharmacists throughout the medication-use process to ensure continuity of care, minimised risk with increasing improvement of patient outcomes. The study aimed to provide insight into the pressing issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…South Africa has two sectors for healthcare, the private healthcare sector serving only approximately 15% of the population and the public healthcare sector responsible for the majority [ 20 , 21 ]. Bronkhorst and colleagues (2021) [ 28 ] found that staff-shortages are more pronounced in the public than in private institutional sectors. South Africa’s National Department of Health (NDoH) introduced the National Health Insurance (NHI) and its pilot phase commenced in 2012 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…South Africa has two sectors for healthcare, the private healthcare sector serving only approximately 15% of the population and the public healthcare sector responsible for the majority [ 20 , 21 ]. Bronkhorst and colleagues (2021) [ 28 ] found that staff-shortages are more pronounced in the public than in private institutional sectors. South Africa’s National Department of Health (NDoH) introduced the National Health Insurance (NHI) and its pilot phase commenced in 2012 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to bridge the gap, the private sector has created ward-based pharmacist or clinical practice pharmacist posts. Clinical pharmacists across public and private sectors have been reported to perform a variety of functions at ward level [ 28 ]. Among individuals not appointed in dedicated clinical pharmacy positions, higher amotivation (lack or absence of motivation) for delivering clinical pharmacy services were found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hospital pharmacy in China and South Africa started in the 1980s and their development was limited by the level of the medical system, leading to the undeveloped prescription refill system. ( 17 , 18 ). In addition, due to the limitations of the included article language, few studies from Japan and other countries were included.…”
Section: Discussionmentioning
confidence: 99%
“…The United States was the most productive country with 172 publications, followed by the United Kingdom (41 publications), Sweden (20 publications), Canada (18 publications), the Netherlands (16 publications), Australia (14 publications), South Africa (10 publications), China (9 publications), Ireland (6 publications), and Switzerland (6 publications) (Figure 3B). The United States (33), the United Kingdom (18), Sweden (11), and the Netherlands (11) ranked as the top three high H-index countries, while the United States was top 1 (Figure 3A). The top three countries in the total number of citations were the United States (5,191 citations and 5,067 without self-citations), the United Kingdom (923 citations and 882 without self-citations), and Sweden (432 citations and 406 without self-citations), whereas the United States (30.18 citations), the Netherlands (23.81 citations), and the United Kingdom (22.84 citations) were the top three countries in average citations per publication (Figure 3A).…”
Section: Countriesmentioning
confidence: 99%